Electrolyte for electrochemical device, plastic composition, use and manufacturing method

A polymer-enhanced electrolyte solution with specific cations, anions, and solvents addresses salting out issues in high-concentration electrolytes, maintaining performance benefits and facilitating easy manufacturing of electrochemical devices.

JP7601086B2Active Publication Date: 2024-12-17ZEON CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022503710
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2021-02-25
Publication Date
2024-12-17
Estimated Expiration
2041-02-25

AI Technical Summary

Technical Problem

Highly concentrated electrolytes in electrochemical devices cause salting out due to high salt concentrations, leading to decreased performance and manufacturing difficulties, such as reduced fluidity and difficulty in injection into device housings, and are prone to salting out during temperature fluctuations.

Method used

Incorporating a specific polymer into the electrolyte solution with a mass average molecular weight of more than 10,000, along with a cation, anion, and solvent, to create a highly viscous electrolyte that suppresses salting out and allows for easy manufacturing of electrochemical device components through molding.

Benefits of technology

The solution maintains the benefits of high-concentration electrolytes like improved voltage resistance and reduced flammability while preventing salting out, enabling easy manufacturing and prolonged device life with enhanced electric potential and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601086000001
    Figure 0007601086000001
  • Figure 0007601086000002
    Figure 0007601086000002
  • Figure 0007601086000003
    Figure 0007601086000003
Patent Text Reader

Abstract

An electrolyte solution for electrochemical devices, said electrolyte solution containing cations (C) that are monovalent to trivalent metal ions, anions (A), a solvent (SO) that is a compound having a molecular weight of 1,000 or less, and a soluble polymer (P) having a mass average molecular weight of more than 10,000, wherein relative to 1 mole of the cations (C), the content ratio of the solvent (SO) is from 0.5 to 4 moles and the content ratio of the polymer (P) is 0.5% by mass or more. The present invention also provides: a thermoplastic composition, an electrode sheet, an insulating layer and an electrochemical device, each of which contains this electrolyte solution; and production methods thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid electrolyte for electrochemical devices, a plastic composition, an electrode sheet for electrochemical devices, an insulating layer for electrochemical devices, methods for producing these, and an electrochemical device. [Background technology]

[0002] Regarding electrolytes used as components of electrochemical devices, so-called high-concentration electrolytes are known, which have extremely high salt concentrations compared to salt concentrations that have been conventionally considered optimal. It has been reported that high-concentration electrolytes may have effects such as improved voltage resistance, reduced flammability, and improved transport number compared to conventional dilute electrolytes (Patent Document 1 and Non-Patent Document 1). Therefore, when such electrolytes are applied to electrochemical devices, it is expected that effects such as longer life, reduced flammability, and higher potential of the device can be obtained. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2015-133312 A [Non-patent literature]

[0004] [Non-Patent Document 1] Electrochemistry, 82(12),1085-1090(2014) Summary of the Invention [Problem to be solved by the invention]

[0005] High-concentration electrolytes are prone to salting out due to their extremely high salt concentration, and once salt crystals are formed by salting out, they are difficult to redissolve. If such salting out occurs in an electrolyte in an electrochemical device and the presence of crystals is maintained without being redissolved, problems such as a decrease in electrolyte performance and damage to the device due to salt crystals may occur. In particular, during transportation or storage of the device, the device may be temporarily exposed to a temperature environment that is much lower than the temperature in normal use. Furthermore, if such salting out occurs in the electrolyte prior to the manufacture of an electrochemical device, fluctuations in concentration, a decrease in fluidity, etc. may occur, hindering the manufacture.

[0006] In addition, the high-concentration electrolyte has a higher viscosity than the conventional dilute electrolyte, which makes it difficult to inject the high-concentration electrolyte into the gap inside the housing of the device, as is the case with the conventional electrolyte, during the manufacture of the electrochemical device.

[0007] Therefore, an object of the present invention is to provide an electrolyte for electrochemical devices which suppresses the occurrence of salting out while enjoying the advantageous effects of a high-concentration electrolyte, such as improved voltage resistance, reduced flammability, improved transport number, etc.; a material for constituting an electrochemical device in a form in which such an electrolyte can be easily utilized; and methods for producing the same.

[0008] A further object of the present invention is to provide an electrode sheet for an electrochemical device, an insulating layer for an electrochemical device, which can provide effects such as a longer device life, flame retardancy, and higher potential, and which can be easily manufactured, methods for manufacturing the same, and an electrochemical device. [Means for solving the problem]

[0009] As a result of investigations aimed at solving the above problems, the present inventors have found that salting out can be suppressed by further adding a specific polymer to a high-concentration electrolyte solution.

[0010] A high-concentration electrolyte containing such a polymer has an even higher viscosity, but as a solution to this problem, the present inventors came up with the idea of ​​mixing such a high-concentration electrolyte with a solid such as an active material to form a plastic composition. That is, when manufacturing a component of a device such as an electrode, the plastic composition can be molded into the shape of the desired component, making it easy to manufacture the device. Based on these findings, the present inventors have completed the present invention. That is, the present invention is as follows.

[0011] [1] A cation (C) which is a monovalent to trivalent metal ion; An anion (A); A solvent (SO) which is a compound having a molecular weight of 1000 or less; An electrolyte solution for an electrochemical device, comprising: a soluble polymer (P) having a mass average molecular weight of more than 10,000; the content ratio of the solvent (SO) relative to 1 mole of the cation (C) is 0.5 to 4 moles, The electrolyte solution has a content of the polymer (P) of 0.5% by mass or more. [2] The electrolyte solution according to [1], having a viscosity of 500 cP or more. [3] The electrolyte solution according to [1] or [2], wherein the anion (A) is a boron atom, a fluorine atom, a phosphorus atom, or an anion containing two or more of these. [4] The anion (A) is (B(R X ) n1 -F) - , (P(R X ) n2 -F) - , (B(R X ) n3 ) - and mixtures thereof; R X represents a monovalent or divalent group, which may be the same or different when a plurality of groups are present, the monovalent group is a halogen atom, an alkyl group, an alkenyl group, an alkynyl group, or a monovalent organic ether group; the divalent group is an alkylene group, an alkenylene group, an alkynylene group, a divalent organic ether group, or an oxo group; the alkyl group, the alkenyl group, the alkynyl group, the monovalent organic ether group, the alkylene group, the alkenylene group, the alkynylene group, and the divalent organic ether group may be substituted with a halogen atom or an oxo group, or may have a heteroatom intervening in a part of the chain; n1 is R X If all are singly-valued, then it is 3, and R X If one of is divalent and the other is monovalent, then it is 2; n2 is R X If all are singly-valued, then it is 5, and R X If one of the two is bivalent and the other is monovalent, then the value is 4; R X If two of the are divalent and the others are monovalent, then the number is 3; n3 is R X If all are singly-valued, then it is 4, and R X If one of the two is bivalent and the other is monovalent, then the value is 3; R X If two of the are divalent, then the value is 2. The electrolyte solution according to [3]. [5] The anion (A) is PF 6 - , B.F. 4 - The electrolyte solution according to [4], comprising an anion selected from the group consisting of a difluoro(oxalato)borate ion, a bis(oxalato)borate ion, and a mixture thereof. [6] The electrolyte solution according to any one of [1] to [5], wherein the solvent (SO) contains a flame-retardant solvent selected from the group consisting of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, trimethyl phosphite, triethyl phosphite, tripropyl phosphite, tributyl phosphite, triphenyl phosphate, triphenyl phosphite, phosphazene-containing compounds, substituted compounds having a substituent in a part of the hydrocarbon chain of these compounds, and mixtures thereof. [7] The electrolyte solution according to any one of [1] to [6], wherein the polymer (P) is a copolymer. [8] The electrolyte solution according to any one of [1] to [7], wherein the cation (C) contains a divalent or trivalent metal ion. [9] The electrolyte solution according to any one of [1] to [8], wherein the polymer (P) has a mass average molecular weight of 100,000 or more.

[10] A method for producing the electrolyte solution according to any one of [1] to [9], A production method comprising a step of dissolving, in the solvent (SO), one or more materials containing the cation (C) and the anion (A), and the polymer (P).

[11] The anion (A) includes a first anion (A1) and a second anion (A2), the first anion (A1) is an anion contained in the anion (A) at the largest molar ratio, the second anion (A2) is an anion having a molar ratio next to that of the first anion in the anion (A), The method according to

[10] , comprising the steps of adding a salt containing the second anion (A2) to the solvent (SO), and then adding a salt containing the first anion (A1).

[12] The production method according to

[10] or

[11] , comprising dissolving a salt containing the cation (C) and the anion (A) in the solvent (SO), and then distilling off the solvent (SO).

[13] A plastic composition for an electrochemical device, comprising the electrolytic solution according to any one of [1] to [9] and a solid material, and having plasticity.

[14] The plastic composition according to

[13] , wherein the solid material contains an active material.

[15] The plastic composition according to

[13] , wherein the solid material comprises an inorganic solid electrolyte (SE).

[16] The plastic composition according to any one of

[13] to

[15] , wherein the solid material contains a fibrous material.

[17] The plastic composition according to

[16] , wherein the fibrous material has an average fiber diameter of 100 nm or less.

[18] The plastic composition according to

[16] or

[17] , wherein the fibrous material is selected from the group consisting of polytetrafluoroethylene fibers, cellulose nanofibers, carbon nanotubes, and combinations thereof.

[19] The plastic composition according to any one of

[16] to

[18] , wherein the fibrous material is a single-walled carbon nanotube.

[20] The plastic composition according to any one of

[13] to

[19] , wherein the solid material comprises a particulate solid material and a fibrous material, and the fibrous material is present in a state of bridging between particles of the particulate solid material.

[21] An electrode sheet for electrochemical devices, comprising the plastic composition according to any one of

[13] to

[20] .

[22] An insulating layer for an electrochemical device, comprising the plastic composition according to any one of

[13] to

[20] .

[23] A method for producing an electrode sheet for electrochemical devices, comprising molding the plastic composition according to any one of

[13] to

[20] into the shape of an electrode sheet.

[24] A method for producing an insulating layer for an electrochemical device, comprising molding the plastic composition according to any one of

[13] to

[20] into a shape of an insulating layer.

[25] An electrochemical device comprising the electrode sheet for electrochemical devices according to

[21] , the insulating layer for electrochemical devices according to

[22] , or both of them.

[26] The electrochemical device according to

[25] , which is a bipolar type. Effect of the Invention

[0012] According to the present invention, there are provided an electrolyte solution for electrochemical devices which provides advantageous effects of a high-concentration electrolyte solution, such as improved voltage resistance, reduced flammability, improved transport number, and the like, while suppressing the occurrence of salting out; a plastic composition for constituting an electrochemical device in a form in which such an electrolyte solution can be easily utilized; and methods for producing the same.

[0013] The present invention further provides an electrode sheet for an electrochemical device, an insulating layer for an electrochemical device, which can provide effects such as a longer device life, improved flame resistance, and higher potential, and which can be easily manufactured, methods for manufacturing the same, and an electrochemical device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, the present invention will be described in detail with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples described below, and may be modified and implemented as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto.

[0015] [1. Electrolyte] The electrolyte of the present invention is an electrolyte for electrochemical devices, which contains a specific cation (C), an anion (A), a specific solvent (SO), and a specific polymer (P).

[0016] [1.1. Cation (C)] The cation (C) is a monovalent to trivalent metal ion. That is, the cation (C) may be one or more kinds of monovalent metal ions, one or more kinds of divalent metal ions, one or more kinds of trivalent metal ions, or a combination thereof. In the electrolyte, the cation (C) may be present in ionization equilibrium with the anion (A). The cation (C) may form a salt with the anion (A), but is usually a compound that can maintain a state in which at least a part of it is dissolved in the solvent (SO) without salting out under temperature and pressure conditions from the production of the electrolyte to the production of an electrochemical device using the electrolyte. More specifically, the cation (C) may be a compound that can maintain a state in which at least 1 mass % is dissolved in the solvent (SO) at normal temperature and normal pressure, for example, at 25°C and 1 atm. Examples of the cation (C) include cations contained in various known salts that can be used in electrolytes for electrochemical devices.

[0017] Cation (C) is preferably an ion selected from the group consisting of alkali metal ions, alkaline earth metal ions, aluminum ions, and combinations thereof. Examples of alkali metal ions include Li + , Na + , K + , Cs + Examples of alkaline earth metal ions include Mg 2+ , Ca 2+ Among them, when the electrochemical device composed of the electrolyte is a secondary battery, Li + , Mg 2+ and combinations thereof are preferred, Li + , and Li + and Mg 2+ A combination with is more preferred.

[0018] The electrolyte of the present invention may contain cations other than the cation (C). However, even in this case, the proportion of the cation (C) in the entire electrolyte is preferably 2.5 mol / L or more in order to exert the effect of the electrolyte. The upper limit of the proportion of the cation (C) is not particularly limited, but may be, for example, 10 mol / L or less.

[0019] The cation (C) may contain a divalent or trivalent metal ion. In terms of designing an electrochemical device, it may be preferable for the cation (C) to contain a divalent or trivalent metal ion rather than a monovalent metal ion alone. However, divalent and trivalent metal ions are prone to salting out. By adopting the composition of the present invention as the electrolyte, it is possible to suppress salting out while enjoying the effects of the divalent and trivalent metal ions. As a specific example, Li is used as the cation (C). + and Mg 2+ When used in combination with Li + In some cases, it may be possible to suppress the precipitation of the electrolyte, thereby improving the cycle characteristics and increasing the strength of the electrode.

[0020] [1.2. Anion (A)] The electrolyte solution of the present invention may contain an anion (A). The anion (A) may contain an anion introduced into the system as a counter anion for the cation (C) and other cations as optional components.

[0021] Examples of the anion (A) include anions contained in various known salts that can be used in electrolytes for electrochemical devices. More specific examples include various anions containing a boron atom, a fluorine atom, a phosphorus atom, or two or more of these.

[0022] Preferred examples of the anion contained in the anion (A) include (B(R X ) n1 -F) - , (P(R X ) n2 -F) - , (B(R X ) n3 ) - When these anions are used as the anion (A), the effect of reducing corrosion of the current collector foil can be obtained.

[0023] R X is a monovalent group or a divalent group, which may be the same or different when a plurality of n1 is present. The monovalent group is a halogen atom, an alkyl group, an alkenyl group, an alkynyl group, or a monovalent organic ether group, and the divalent group is an alkylene group, an alkenylene group, an alkynylene group, a divalent organic ether group, or an oxo group. The alkyl group, the alkenyl group, the alkynyl group, the monovalent organic ether group, the alkylene group, the alkenylene group, the alkynylene group, and the divalent organic ether group may be substituted with a halogen atom or an oxo group, and a heteroatom may be present in a part of the chain. n1 is R X If all are singly-valued, then it is 3, and R X If one of the two is bivalent and the other is monovalent, n2 is 2, and R X If all are singly-valued, then it is 5, and R X If one of the two is bivalent and the other is monovalent, then the value is 4; R X If two of the are divalent and the other is monovalent, n3 is 3, and R X If all are singly-valued, then it is 4, and R XIf one of the two is bivalent and the other is monovalent, then the value is 3; R X If two of them are divalent, the number is 2.

[0024] R X When is a monovalent group, preferred examples thereof include a fluorine atom, -CF 3 , -C 2 F 5 , -CN.

[0025] R X When is a divalent group, preferred examples thereof include an oxo group (=O), -O-CO-CO-O-, -O-CO-CH 2 -CO-O-. X When is a divalent group, each of the divalent bonds may be bonded to a boron atom or a phosphorus atom.

[0026] (B(R X ) n1 -F) - , (P(R X ) n2 -F) - , and (B(R X ) n3 ) - A more specific example of this is PF 6 - (R X Both are F, n2=5), BF 4 - (R X are F, n3=4), difluoro(oxalato)borate ion (DFOB, R X Two of them are -F and one is -O-CO-CO-O-, n3=3), and bis(oxalate)borate ion (R X Two of these are -O-CO-CO-O-, n3=2), and mixtures thereof.

[0027] When the anion (A) contains a plurality of cations, the anion with the largest molar content among the anions (A) is called the first anion (A1), the anion with the second largest molar content after the first anion (A1) is called the second anion (A2), the anion with the second largest molar content after the second anion (A2) is called the third anion (A3), etc. In this case, it is preferable to select an anion that contributes to ionic conductivity and has high ionic conductivity as the first anion (A1). Specific examples of anions that can exert such an effect include bis(fluorosulfonyl)imide ion (FSI), bis(trifluoromethanesulfonyl)imide ion (TFSI), BF 4 - , difluoro(oxalato)borate ion, and mixtures thereof.

[0028] On the other hand, the second anion (A2) may be added in combination with the first anion (A1) to provide an additional effect. Examples of such effects include corrosion inhibition of the current collector and stabilization by coating the surface of the active material. Examples of anions that can provide such effects include BFx, PFx, difluoro(oxalato)borate ion, bisoxalateborate ion, and mixtures thereof. Here, the BFx type refers to one or a mixture of two or more of various anions in which one anion contains a combination of one boron atom and one to four fluorine atoms, and the PFx type refers to one or a mixture of two or more of various anions in which one anion contains a combination of one phosphorus atom and one to six fluorine atoms.

[0029] The proportion of the anion (A) in the electrolytic solution of the present invention is not particularly limited, and may be, for example, an equal amount to the cation (C) and other optional cations.

[0030] [1.3. Solvent (SO)] The solvent (SO) is a compound having a molecular weight of not more than 1000. The lower limit of the molecular weight of the solvent (SO) is not particularly limited, but may be, for example, 40 or more.

[0031] The solvent (SO) may be water, a hetero element-containing organic compound (O), or a mixture thereof. The hetero element-containing organic compound (O) may preferably be a compound that does not have an ionic group. That is, the hetero element-containing organic compound (O) may be a compound other than a compound that has an ionic group. Here, the compound that has an ionic group is a cation or an anion, and includes a compound that has multiple ionic groups in the molecule, and a betaine that has a positive and negative charge.

[0032] Examples of the solvent (SO) include various compounds known to be usable as a solvent in an electrolytic solution for electrochemical devices. Among them, one or more compounds having performance according to a desired application can be appropriately selected and used in combination as necessary. For example, when it is desired to increase the ionic conductivity of the electrolytic solution, an organic solvent having a low boiling point or a mixed solvent containing a high ratio of an organic solvent having a low boiling point can be used as the solvent (SO). Examples of such organic solvents having a low boiling point include dimethyl carbonate, monoglyme, methyl formate, methyl acetate, methyl alcohol, acetonitrile (AN), and mixtures thereof.

[0033] At least one solvent is preferably selected from compounds (SO-S) that are solid at room temperature and 1 atm and become liquid when mixed with a cation (C) and an anion (A). Even if the solvent evaporates and diffuses into the surroundings due to overheating during the manufacturing process or heat generated by a malfunction of an electrochemical device, the compound that has the property of becoming solid at around room temperature can be condensed as a solid and does not leak widely into the surroundings, so it is highly safe. Here, room temperature refers to a range around 25°C, more specifically 25°C, and it is preferable that the compound is solid even at higher temperatures. The preferred melting point of the compound is 5°C or higher, more preferably 25°C or higher, and even more preferably 40°C or higher. The upper limit of the melting point is not particularly limited, but can be, for example, 200°C or lower. The ratio of the compound (SO-S) to the entire solvent (SO) is preferably 50 mol% or higher, more preferably 60 mol%, even more preferably 70 mol% or higher, and may be 100 mol%. Examples of the compound (SO-S) include ethylene carbonate (EC), N-methyloxazolidone, N,N-dimethylimidazolidinone, sulfolane (SL), dimethylsulfone, malononitrile, succinonitrile, and dimethyl oxalate. The compound (SO-S) is a solid at room temperature, but when mixed with a salt, it dissolves and becomes liquid, forming an electrolyte.

[0034] When it is desired to reduce the flammability of the electrolyte, a high boiling organic solvent and / or water, or a mixed solvent containing a high boiling organic solvent and / or water in a high ratio, can be used as the solvent (SO). The boiling point of such a high boiling organic solvent can be preferably 130°C or higher, more preferably 160°C or higher, and even more preferably 200°C or higher. The upper limit of the boiling point is not particularly limited, but can be, for example, 350°C or lower. Specific examples of organic solvents with high boiling points include γ-butyrolactone, propylene carbonate, ethylene carbonate (EC), N-methyloxazolidone, N,N-dimethylimidazolidinone, dimethylsulfone (DMS), sulfolane (SL), dimethylsulfone, malononitrile, succinonitrile, dimethyl malonate, dimethyl oxalate, diglyme, triglyme, tetraglyme, and mixtures thereof.

[0035] In addition to or instead of the organic solvent with a high boiling point, a flame-retardant solvent may be used. Examples of the flame-retardant solvent include trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, trimethyl phosphite, triethyl phosphite, tripropyl phosphite, tributyl phosphite, triphenyl phosphate, triphenyl phosphite, and a phosphazene-containing compound. Further examples of the flame-retardant solvent include substituted compounds having a substituent in a part of the hydrocarbon chain of the above-mentioned various compounds. Furthermore, a mixture of two or more of the above-mentioned compounds and substituted compounds may be used. Examples of the substituent include halogen atoms such as fluorine atoms, chlorine atoms, and bromine atoms. When the flame retardant is a phosphate ester or a phosphite ester, it is preferable that the alkyl group is substituted with a halogen atom because the flame retardant effect is high. Specific examples of the phosphazene-containing compound include monoethoxypentafluorocyclotriphosphazene, diethoxytetrafluorocyclotriphosphazene, and monophenoxypentafluorocyclotriphosphazene. When the solvent (SO) contains a flame-retardant solvent, the content of the flame-retardant solvent in the entire solvent (SO) may be 0.5 to 20 mass %.

[0036] In a preferred example, the solvent (SO) contains a cyclic carbonate. In particular, when the negative electrode material of the electrochemical device is a graphite-based material, the electrolyte contains a cyclic carbonate as the solvent (SO), which reduces the irreversible capacity of the negative electrode during initial charging. Specific examples of the cyclic carbonate include ethylene carbonate, vinylene carbonate, vinylethylene carbonate, and compounds having the structures thereof.

[0037] Furthermore, when the electrochemical device is a secondary battery such as a lithium ion secondary battery, examples of preferred solvents (SO) include acetonitrile, ethyl methyl carbonate, ethylene carbonate, sulfolane, dimethyl sulfone, gamma butyrolactone, fluoroethylene carbonate, succinonitrile, N-methyloxazolidone, N,N-dimethyloxazolidinone, trimethyl phosphate, and mixtures thereof.

[0038] The electrolyte of the present invention may contain, in addition to the solvent (SO), a liquid compound having a molecular weight of more than 1000 and less than 100,000. Even in this case, however, the proportion of the cation (C) in the entire electrolyte is preferably 2.5 mol / L or more.

[0039] In the electrolytic solution of the present invention, the content ratio of the solvent (SO) to the cation (C) is within a specific range. That is, the content ratio of the solvent (SO) to 1 mole of the cation (C) is 0.5 moles or more, preferably 1 mole or more, more preferably 1.5 moles or more, and is 4 moles or less, preferably 3.5 moles or less, more preferably 3.0 moles or less. By setting the content ratio of the solvent (SO) to the cation (C) to a large value equal to or greater than the lower limit, the ion conductivity can be increased, and the performance of the electrochemical device can be easily improved. By setting the content ratio of the solvent (SO) to the cation (C) to a small value equal to or less than the upper limit, the volatility, flame retardancy, and oxidation resistance of the electrolytic solution can be improved.

[0040] [1.4. Polymer (P)] The polymer (P) is a soluble polymer. The solubility of the polymer (P) here means that the polymer (P) maintains a dissolved state in the electrolytic solution under temperature and pressure conditions from the production of the electrolytic solution to the production of an electrochemical device using the same. More specifically, when the polymer (P) is added to a solvent (SO) at room temperature and normal pressure, for example, 25°C and 1 atm, and at least 1 mass % of the polymer (P) can be maintained dissolved in the solution, the polymer can be considered to be a soluble polymer.

[0041] The polymer (P) has a mass average molecular weight of more than 10,000, preferably 100,000 or more, more preferably 200,000 or more, even more preferably 300,000 or more, and even more preferably 400,000 or more. On the other hand, the upper limit of the mass average molecular weight can be preferably 10 million or less, more preferably 3 million or less. By setting the mass average molecular weight to the lower limit or more, the viscosity of the electrolyte can be greatly increased with a small amount of addition, and salting out can be effectively suppressed. By setting the mass average molecular weight to the upper limit or less, the electrolyte can be easily maintained in a liquid state. The molecular weight of the polymer (P) can be measured, for example, in accordance with JIS K7252.

[0042] Examples of the polymer (P) include polyether polymers, acrylic polymers, polyacrylonitrile polymers, polyoxazoline polymers, aliphatic polycarbonate polymers, and mixtures thereof. More specific examples include polyethylene oxide, ethylene oxide copolymers, side-chain ethylene oxide polymers, hydrin rubber, polyvinyl acetate, vinyl chloride-vinyl acetate copolymers, poly2-ethyl-2-oxazoline, poly2-methyl-2-oxazoline, polyoxazolidinone, side-chain oxazoline copolymers, poly-N-vinylacetamide, polyvinylpyrrolidone, polyacrylonitrile, nitrile rubber, acrylic acid ester copolymers, polymethyl methacrylate, styrene-acrylate copolymers, and acrylic rubber. These polymers may be used alone or in combination of two or more.

[0043] The polymer (P) preferably has a hetero element in the main chain. Examples of the main chain structure having a hetero element include -O- and -N-. A polymer having a hetero element in the main chain has a high affinity with the solvent (SO), and therefore tends to be dissolved in the solvent (SO) at a low temperature and with a small power in the production of an electrolyte, and is also preferable because it can dissolve the polymer (P) at a high concentration. Examples of preferred polymers include, for example, ethylene oxide-based polymers and oxazoline-based polymers. The polymer (P) is more preferably a copolymer. Compared with homopolymers, copolymers tend to have lower crystallinity, and therefore tend to be more easily dissolved in the solvent (SO) during the production of the electrolyte solution, and are particularly preferred because the polymer (P) itself is less likely to crystallize and precipitate in the electrolyte solution. Examples of preferred copolymers include polyether-based copolymers such as ethylene oxide-propylene oxide copolymers, and oxazoline-based copolymers such as (2-ethyl-2-oxazoline)-(2-methyl-2-oxazoline) copolymers.

[0044] The content of the polymer (P) in the electrolytic solution of the present invention is 0.5% by mass or more, preferably 1% by mass or more, more preferably 2% by mass or more, and preferably 40% by mass or less, more preferably 20% by mass or less. By making the content ratio equal to or more than the lower limit, a high salting-out suppression effect can be obtained. By making the content ratio equal to or less than the upper limit, a large decrease in ion conductivity can be suppressed, and the liquid state of the electrolytic solution can be easily maintained.

[0045] [1.5. Properties of electrolyte] The electrolyte of the present invention has a viscosity of preferably 500 cP or more, more preferably 700 cP or more, and preferably 10 million cP or less, more preferably 1 million cP or less. By having the viscosity of the electrolyte at 25 ° C. be equal to or more than the lower limit, a high salting-out suppression effect can be obtained. In particular, even if a precipitate occurs as a result of salting out, the size of the precipitate can be made small. Although not bound by a specific theory, it is believed that such an effect is due to the fact that in a highly viscous solution, the movement of the solute is hindered during the salting out process, and as a result, the precipitate precipitates without forming a large mass. In addition, when the viscosity of the electrolyte is equal to or more than the lower limit, the seepage of the electrolyte from the electrode is suppressed, which is effective in stabilizing the operation of the electrochemical device and preventing leakage. However, when the viscosity exceeds 700 cP, the time required for injecting the electrolyte into the porous electrode becomes considerably long, so an electrode manufacturing method that does not perform the injection process may be selected. On the other hand, when the viscosity of the electrolyte is equal to or less than the upper limit, the flow state of the electrolyte can be easily maintained. Although the electrolyte may be in a gelled state after losing fluidity, the electrolyte may be used as the electrolyte of the present invention. However, gelation reduces the ionic conductivity. Therefore, regardless of the appearance of the electrolyte, the electrolyte may be used as the electrolyte when the ionic conductivity of the electrolyte at 25° C. is 10 -4 The upper limit of the ionic conductivity is preferably 10 S / cm or more. -1 It can be less than S / cm. In particular, during the production of electrodes or insulating layers for electrochemical devices, it is essential that the electrolyte has fluidity, and the viscosity may be controlled within the above range by increasing the processing temperature. The viscosity in the present invention refers to the viscosity measured at 1000 rpm using an EMS viscometer (Kyoto Electronics Manufacturing, EMS-1000S) under sealed conditions so that the composition of the electrolyte does not change and moisture in the air does not get mixed in. The viscosity measured by this measurement method is basically the same as the value measured in accordance with JIS Z8803. If the viscosity of the electrolyte is too high to measure at the operating temperature, it is found that the viscosity at 25°C is higher if the temperature is raised to the operating temperature. It is also possible to measure several points at high temperatures and extrapolate the viscosity to the operating temperature. If the measurement is still difficult, a different viscometer compatible with high viscosity may be used after checking the deviation from the viscosity measured by this device.

[0046] 2. Manufacturing method of electrolyte solution The electrolyte solution of the present invention may be produced by any production method, but it can usually be produced by a production method including a step of dissolving one or more materials containing a cation (C) and an anion (A) and a polymer (P) in a solvent (SO). This will be described below as the production method of the electrolyte solution of the present invention.

[0047] As a material containing a cation (C) and an anion (A), it is preferable to use a salt in which these are paired from the viewpoint of ease of operation. Examples of such salts include salts in which any one or more of the specific examples of the cation (C) described above are paired with any one or more of the specific examples of the anion (A) described above. The amount of salt added can be adjusted so that the relative ratio of the solvent (SO) and the cation (C) in the resulting electrolyte solution is a desired value. The salt used in the production is usually in a crystalline state. The smaller the grain size of the crystals, the more preferable it is from the viewpoint of promoting dissolution. Specifically, the size of the crystals can be preferably 5 mm or less, more preferably 1 mm or less, and even more preferably 500 μm or less. The size of the crystals referred to here can be the length in the longest direction when the crystals are observed from various angles. The lower limit of the size of the crystals is not particularly limited, but can be, for example, 0.5 μm or more.

[0048] The order of dissolving the solute (salt, polymer (P), etc.) in the solvent (SO) is not particularly limited, and any order that achieves easy dissolution may be used. In particular, when the anion (A) contains the above-mentioned first anion (A1) (i.e., the anion with the largest molar content) and the second anion (A2) (i.e., the anion with the next largest molar content), it is preferable to add the salt containing the second anion (A2) first and then add the salt containing the first anion (A1), since this makes it easier to achieve easy dissolution.

[0049] From the viewpoint of promoting dissolution of the solute in the solvent (SO), a dilute solution may be prepared once, and then a part of the solvent may be distilled off to concentrate the concentration. That is, when it takes a long time for the salt and polymer (P) to dissolve in the solvent (SO) to a high concentration, and a short time for dissolving in a low concentration, and the solvent can be easily distilled off, it is possible to shorten the time required for producing an electrolyte by preparing a dilute solution once, and then distilling off a part of the solvent to concentrate the concentration. The concentration of the solute in the dilute solution once prepared may be, for example, 1 / 20 to 1 / 2 of the desired concentration in the electrolyte, more preferably 1 / 15 to 1 / 5.

[0050] [3. Plastic composition] The plastic composition of the present invention is a plastic composition for electrochemical devices, which contains the electrolytic solution of the present invention and a solid material and has plasticity. The solid material is an object that can maintain a solid state in the plastic composition under the temperature and pressure conditions during use of the electrochemical device. More specifically, the solid material can be an object that can maintain a solid state in the plastic composition at room temperature and normal pressure, for example, 25°C and 1 atm. The plastic composition is a solid having plasticity as a whole, but since it is actually a mixture of a solid material and a liquid electrolytic solution, it can be separated and recovered. The plastic composition may contain only one type of solid material, or may contain multiple types of solid materials. The plastic composition contains such a solid material and an electrolyte that is liquid when not mixed with the solid material, and as a whole, the plastic composition becomes a solid that has plasticity by itself.

[0051] The solid matter may specifically include an active material and / or an inorganic solid electrolyte (SE). The active material is a material that can function as an electrode active material for a positive or negative electrode in an electrochemical device. Specific examples of the active material include lithium oxides such as lithium cobalt oxide, graphite, activated carbon, graphene, silicon and its oxides, tin and its oxides, sulfur, organometallic complexes, MOFs (Metal-Organic-Frameworks), and Prussian blue analogues.

[0052] The active material is preferably in a particulate form, more preferably with a volume average particle diameter of 30 μm or less, and even more preferably with a shape of 20 μm or less. The lower limit of the particle diameter is not particularly limited, but may be, for example, 0.05 μm or more. From the viewpoint of increasing the electrode strength, it is preferable to use a nano-sized active material, which increases the contact interface area with other components of the plastic composition, thereby increasing the strength of the obtained electrode and improving the ability to promote the electrochemical reaction of the electrode. The volume average particle diameter of the active material and other particles can be measured in accordance with JIS K8825.

[0053] The inorganic solid electrolyte (SE) is a substance that can function as a component for increasing the ionic conductivity of an insulating layer in an electrochemical device, that is, a layer separating a positive electrode and a negative electrode. In many cases, the inorganic solid electrolyte (SE) is non-flammable or has low flammability, so the higher the ratio of the inorganic solid electrolyte (SE) mixed with the electrolytic solution, the higher the safety of the electrochemical device. The preferred mixing ratio of the inorganic solid electrolyte (SE) per total volume of the electrolytic solution and the inorganic solid electrolyte (SE) is preferably 10 vol% or more, more preferably 30 vol% or more, even more preferably 50 vol% or more, and particularly preferably 70 vol% or more. The upper limit of the preferred mixing ratio of the inorganic solid electrolyte (SE) per total volume of the electrolytic solution and the inorganic solid electrolyte (SE) is not particularly limited, but may be, for example, 99 vol% or less. Specific examples of inorganic solid electrolytes (SEs) include lithium ion conductive metal oxide inorganic solid electrolytes (SEs) and sodium ion conductive inorganic solid electrolytes (SEs). Examples of lithium ion conductive metal oxide inorganic solid electrolytes (SEs) include LAGP (Li 1.5 Al 0.5 Ge 1.5 P 3 O 12 ), LLZ(Li 7 La 3 Zr 2 O 12 ), LLZTO(Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 ), LLT(LiLa 0.51 TaO 2.94 ), LASTP(Li 2 Al 2 SiP 2 TiO 13 ), LTAP(Li 1.4 Ti 1.6 Al 0.4 P 3 O 12 ), and Li 2.99 Ba 0.005 O 1+x Cl 1-2x Examples of sodium ion conductive inorganic solid electrolytes (SEs) include β-alumina, Na 2.99 Ba 0.005 O 1+x Cl 1-2x As a lithium ion conductive sulfide-based inorganic solid electrolyte (SE), LPS (Li 7 P 3 S 11 ), LGPS(Li 10 GeP 2 S 12 ), and Li 9.54 S 1.74 P 1.44 S 11.7 Cl 0.3Inorganic solid electrolytes (SEs) are generally solid particles in a crystalline state having the above compositions. Further examples of inorganic solid electrolytes (SEs) include crystals having the above compositions plus small amounts of other elements, and analogs having the above compositions slightly modified. The intragranular ionic conductivity of inorganic solid electrolytes (SEs) is 10 -5 S / cm or more is preferable, and 10 -4 More preferably, it is 10 S / cm or more. -3 S / cm or more is preferable, and 10 -2 The upper limit of the ionic conductivity in the particles of the inorganic solid electrolyte (SE) is not particularly limited, but is, for example, 10 0 It can be less than S / cm. The inorganic solid electrolyte (SE) is preferably in a particulate form, more preferably with a volume average particle diameter of 20 μm or less, and even more preferably with a shape of 10 μm or less. The lower limit of the volume average particle diameter of the inorganic solid electrolyte (SE) is not particularly limited, but may be, for example, 0.01 μm or more. The inorganic solid electrolyte (SE) can also be a component of a plastic composition for forming an electrode sheet. In this case, the inorganic solid electrolyte (SE) can be added as a component of the plastic composition by suspending the inorganic solid electrolyte (SE) in an electrolytic solution and mixing the suspension with other components to produce a plastic composition. When the inorganic solid electrolyte (SE) is used in an electrode sheet, the particle diameter of the inorganic solid electrolyte (SE) is preferably smaller than that of the active material.

[0054] The plastic composition may further include a fibrous material. The fibrous material may constitute a part of the solid matter in the plastic. The fibrous material may also function as an active material or an inorganic solid electrolyte (SE). By including the fibrous material in the plastic composition, it is possible to adjust the viscosity of the plastic composition to a desired range or to impart additional functions to the plastic composition.

[0055] Examples of fibrous materials include polytetrafluoroethylene fibers, cellulose nanofibers, carbon nanotubes, carbon nanofibers, and combinations thereof. Carbon nanotubes are particularly preferably single-walled carbon nanotubes.

[0056] The fiber diameter of the fibrous material is preferably nano-sized (maximum diameter is less than 1 μm). The average fiber diameter of the fibrous material is preferably 0.4 nm or more, preferably 500 nm or less, more preferably 100 nm or less. When the plastic composition contains nano-sized fiber components, the plastic composition is more cohesive, and a molded product having excellent strength can be obtained. The fiber diameter can be measured using a microscope such as a scanning electron microscope or a transmission electron microscope, and the arithmetic average can be calculated. When polytetrafluoroethylene fiber is used as the fibrous material, it is possible to mold the fibrous shape into such a fiber shape in the process of producing the plastic composition. Specifically, in the process of producing the plastic composition, particulate polytetrafluoroethylene is added to the system, and a shear force is further applied by kneading or the like, so that the shape can be changed into a nano-sized fiber in the system.

[0057] The fiber length of the fibrous material is preferably equal to or longer than the volume average particle size of the solid material other than the fibrous material. When the plastic composition is molded to form a member having a layered shape (such as an electrode or an insulating layer), the fiber length of the fibrous material is more preferably equal to or longer than half the average thickness of the member, even more preferably equal to or longer than the average thickness, and may be equal to or longer than the thickness of the member.

[0058] In a preferred embodiment, the solid material includes a particulate solid material and a fibrous material, and in the plastic composition, the fibrous material exists in a state of bridging between particles of the particulate solid material. More specifically, when the electrode of the present invention is observed under a microscope, it is preferable that there are 10 or more bridges in a field of view of 100 μm square, and more preferably there are 20 or more bridges. If there are volatile organic compounds present and the observation is unsuitable, it is preferable to perform the observation after drying. By having such a bridge structure, the cohesion of the plastic composition is further improved, and a molded product having even greater strength can be obtained.

[0059] 4. Electrodes and insulating layers, and their manufacturing methods The electrode sheet for electrochemical devices of the present invention and the insulating layer for electrochemical devices of the present invention contain the plastic composition of the present invention. Also, the method for producing an electrode sheet for electrochemical devices of the present invention comprises forming the plastic composition of the present invention into the shape of an electrode sheet, and the method for producing an insulating layer for electrochemical devices of the present invention comprises forming the plastic composition of the present invention into the shape of an insulating layer.

[0060] The electrode sheet can be laminated with an appropriate layer of a current collector to form an electrode. The current collector can be a metal foil such as copper foil, aluminum foil, or stainless steel foil.

[0061] The shapes of the electrode sheet and the insulating layer are not particularly limited and may be any desired shape. From the viewpoint of obtaining a small-sized, high-performance electrochemical device, the electrode sheet and the insulating layer are preferably in the form of a thin layer. If in the form of a layer, the thickness is preferably 5 to 200 μm. By setting the thickness to the above lower limit or more, it is possible to easily obtain self-supporting properties. By setting the thickness to the above upper limit or less, it is possible to easily form a small-sized, high-performance electrochemical device.

[0062] The electrode sheet for electrochemical devices of the present invention and the insulating layer for electrochemical devices of the present invention preferably have self-supporting properties. Here, self-supporting properties refer to the ability to maintain its shape without tearing even when not supported by a support such as a base film. Specifically, it is preferable that a sample is prepared by cutting the electrode sheet or insulating layer having a layered shape into a rectangular shape, and the shape can be maintained to such an extent that the sample can be lifted while pinching the sides with tweezers. More specifically, it is preferable that such a shape can be maintained in a sample having a rectangular shape of preferably 1 cm square, more preferably 2 cm square. By having such self-supporting properties, it is possible to easily manufacture an electrochemical device and to increase the durability of the obtained electrochemical device.

[0063] [5. Electrochemical Devices] The electrochemical device of the present invention comprises the electrode sheet for electrochemical devices of the present invention, the insulating layer for electrochemical devices of the present invention, or both of them. The electrode sheet can be provided in the electrochemical device in a state in which it is superimposed on an appropriate layered current collector such as those described above to form an electrode. The insulating layer can also be provided between a plurality of electrodes (e.g., positive and negative electrodes) in the electrochemical device.

[0064] Examples of the electrochemical device of the present invention include primary batteries such as lithium primary batteries; non-aqueous secondary batteries such as lithium ion secondary batteries, lithium metal secondary batteries, sodium ion secondary batteries, potassium ion secondary batteries, magnesium secondary batteries, and aluminum secondary batteries; air batteries; solar cells such as dye-sensitized solar cells; capacitors such as electric double layer capacitors and lithium ion capacitors; electrochromic display devices; electrochemical light-emitting devices; electric double layer transistors; and electrochemical actuators.

[0065] In a preferred example, the electrochemical device of the present invention is a battery, specifically a lithium ion secondary battery. More specifically, a positive electrode collector such as aluminum foil, a positive electrode sheet, a separator, a negative electrode sheet, and a negative electrode collector such as copper foil are stacked in this order to form a composite constituting a battery unit, which is inserted into an appropriate exterior, and further an electrolyte solution is injected as necessary, and the opening of the exterior is sealed, thereby manufacturing a battery. Here, a lithium ion secondary battery can be constructed by adopting the electrode sheet or insulating layer of the present invention as one or more of the positive electrode sheet, the negative electrode sheet, and the separator, and using electrolyte and active materials suitable for the electrolyte and active materials of a lithium ion secondary battery as the electrolyte and active materials constituting them. In addition, when an electrolyte solution is injected into the exterior, the electrolyte solution of the present invention may be used as the electrolyte solution.

[0066] In the manufacture of an electrochemical device, a step of causing a reaction such as a crosslinking reaction to proceed on the polymer (P) constituting the electrode sheet and / or insulating layer may be carried out after laminating them. More specifically, after sealing the opening of the exterior, some kind of energy may be applied from outside the exterior to cause the crosslinking reaction of the polymer (P). Examples of the application of such energy include heating and irradiation with energy rays such as visible light, electron beams, and radiation. Among these, an energy that can be applied through the exterior may be appropriately selected. In order to achieve such a crosslinking reaction, the electrolyte may contain a component such as a polymerization initiator that causes the crosslinking reaction of the polymer (P) to proceed in response to the application of such energy.

[0067] In a preferred embodiment, the electrochemical device of the present invention is a bipolar device, specifically a bipolar battery. The bipolar device is a device having an electrode with a bipolar structure. The bipolar electrode is an electrode having a positive electrode material on one side of a current collector and a negative electrode material on the other side. By forming a structure in which a plurality of bipolar electrodes are stacked, a structure in which a plurality of device units are stacked in series can be obtained in one device. For example, in a bipolar battery, a structure in which a plurality of battery units are stacked in series in one battery pack can be obtained. In such a bipolar device, a major issue is to prevent liquid junctions of the electrolyte between the device units, but by employing the electrode and / or insulating layer of the present invention as the electrode and / or insulating layer, such liquid junctions can be easily prevented.

[0068] A more specific example of a bipolar battery is a battery having an electrode laminate in which a positive electrode collector such as aluminum foil, a positive electrode sheet, an insulating layer sheet, a negative electrode sheet, an intermediate foil such as stainless steel foil, a positive electrode sheet, an insulating layer sheet, a negative electrode sheet, and a negative electrode collector such as copper foil are stacked in this order. This example is an example of a structure in which two battery units are stacked in series, but it is also possible to provide one or more combinations of "an intermediate foil such as stainless steel foil, a positive electrode sheet, an insulating layer sheet, and a negative electrode sheet" to have a structure in which three or more battery units are stacked in series. EXAMPLES

[0069] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the examples shown below, and can be modified and carried out as desired without departing from the scope of the claims of the present invention and the scope of equivalents thereto.

[0070] In the following description, the units "%" and "parts" that represent amounts are by weight unless otherwise specified. Furthermore, the operations described below were carried out under room temperature and normal pressure conditions unless otherwise specified.

[0071] The meanings of the abbreviations for the substances used in the examples and comparative examples are as follows. LiFSI: Lithium bis(fluorosulfonyl)imide (Li + (N(SO 2 F) 2 ) - ) LiTFSI: Lithium bis(trifluoromethanesulfonyl)imide (Li + (N(SO 2 CF 3 ) 2 ) - ) LiBF 4 : Lithium fluoride LiDFOB: Lithium difluoro(oxalato)borate (Li + B(R X ) 3 ) - , R X Two of them are -F and one is -O-CO-CO-O-) Mg(TFSI) 2 Magnesium bis(trifluoromethanesulfonyl)imide (Mg 2+ ((N(SO 2 CF 3 ) 2 ) - ) 2 ) AN: Acetonitrile EMC: Ethyl methyl carbonate EC: Ethylene carbonate SL: Sulfolane DMS: dimethyl sulfone GBL: gamma butyrolactone FEC: Fluoroethylene carbonate DMC: Dimethyl carbonate DEC: Diethyl carbonate TMP: Trimethyl phosphate PTFE: Polytetrafluoroethylene Polymer (PA): Ethylene oxide-propylene oxide copolymer Mass average molecular weight: 200,000 Polymer (PB): Ethylene oxide-propylene oxide copolymer Mass average molecular weight: 500,000 Polymer (PC): Ethylene oxide polymer Mass average molecular weight: 1 million Polymer (PD): Poly(2-ethyl-2-oxazoline) Mass average molecular weight: 500,000 Polymer (PE): Polymethyl methacrylate Mass average molecular weight: 100,000 Polymer (PF): Poly(2-ethyl-2-oxazolidinone) Mass average molecular weight: 25,000

[0072] [Production Examples 1 to 14] (P1-1. Preparation of mixed solution) A mixed solution was obtained by mixing a salt containing a cation (C) and an anion (A) shown in Table 1 with a solvent (SO). The mixing ratio was the molar ratio shown in Tables 1 and 2. When mixing, heating was performed appropriately if the dissolution rate was slow at room temperature.

[0073] (P1-2. Determining the presence or absence of precipitates) The mixture obtained in (P1-1) was left to stand at 15°C for 3 days, and then visually observed to determine whether or not a precipitate was present. If a precipitate was determined to be present, the shape and dimensions of the precipitate were also recorded. The precipitate was observed from various angles, and the length in the longest direction was used as the dimension of the precipitate. The results are shown in Table 3.

[0074] [Table 1]

[0075] [Table 2]

[0076] [Table 3]

[0077] Precipitation was observed in all examples except for Production Examples 12 and 13. The precipitates were angular and needle-like in shape, and had dimensions of approximately 1 mm or more. Therefore, when these mixed solutions are used in an electrochemical device, the occurrence of precipitates is considered to adversely affect the function of the device. Production Example 14 is an example in which the cations in Production Example 12 and Production Example 13 are mixed. Although no precipitation was observed in Production Examples 12 and 13, precipitation was observed in Production Example 14, which shows that precipitation is more likely to occur when multiple types of cations are mixed.

[0078] (P1-3. Redissolving by heating) After the determination in (P1-2), the electrolytes containing the precipitates in Production Examples 1 to 11 and Production Example 14 were further heated at 60° C. for 60 minutes. In all cases, it was not possible to redissolve all of the precipitates. This is believed to be due to the large size of the precipitates.

[0079] [Examples 1-1 to 1-22] Polymers (PA) to (PF) (abbreviated simply as "A" to "F" in the table) shown in Table 4 were added to and dissolved in the mixed solutions prepared in (P1-1) of Production Examples 1 to 14, respectively, to prepare electrolyte solutions. The type of mixed solution used, the type of polymer, and the proportion of polymer added (mass %; percentage of polymer (P) in 100 mass % of electrolyte solution) were as shown in Table 1. In each Example, the dissolving step was as follows: Step (i): The temperature of the electrolyte is kept at 25° C., a polymer is added to the electrolyte, and the electrolyte is allowed to stand. Step (ii): The temperature of the electrolyte is kept at 60° C., and the polymer is added to the electrolyte and stirred. Two different processes were tried.

[0080] In both cases where the polymer (PA) and the polymer (PB) were used, a uniform solution was obtained in step (i) by standing for 24 hours in both examples. On the other hand, in step (ii) by stirring for 30 minutes in both examples, a uniform solution was obtained. Furthermore, the viscosity of the obtained electrolyte was measured. The viscosity was measured at 1000 rpm using an EMS viscometer (Kyoto Electronics Manufacturing Co., Ltd., EMS-1000S) under sealed conditions so that the composition of the electrolyte did not change and moisture in the air was not mixed in.

[0081] When the polymer (PC) was used, in all Examples in step (i), transparent insoluble matter remained after 24 hours of standing, and a homogeneous solution was obtained after further standing for 150 hours, whereas in all Examples in step (ii), a homogeneous solution was obtained after 3 hours of stirring.

[0082] When the polymer (PE) was used, the dissolution hardly progressed after 24 hours of standing in step (i), and furthermore, the dissolution did not progress even after 150 hours of standing in step (i). On the other hand, in step (ii), a uniform solution was obtained after 20 hours of stirring.

[0083] In the case of using polymer (PD) and polymer (PF), the dissolution hardly progressed after 24 hours of standing in step (i), and furthermore, the dissolution did not progress even after 150 hours of standing, so the preparation of the electrolyte solution by step (i) was not performed. On the other hand, in step (ii), a uniform solution was obtained after 3 hours of stirring.

[0084] Each of the obtained electrolyte solutions was left to stand at 15° C. for 3 days, and then visually observed to determine whether or not a precipitate was formed. The results are shown in Table 4. Furthermore, the measurement results of the viscosity of the electrolyte solutions are shown in Table 5.

[0085] [Table 4]

[0086] [Table 5]

[0087] In Table 5, * indicates that the viscosity was too high to introduce the sample into the viscosity measuring device and therefore measurement was not possible. Therefore, in these examples, the viscosity was considered to be higher than that of Examples 1-13, which could be measured at room temperature. The samples measured at temperatures higher than 25°C had low fluidity at 25°C, making measurement difficult, and were therefore measured at higher temperatures.

[0088] In the examples where the presence or absence of precipitates was judged to be "present," only very small precipitates were observed. When these electrolytes were used in electrochemical devices, it was judged that such small precipitates would have little adverse effect on the electrochemical device. When the electrolytes in which precipitates were observed were heated to 60°C, the precipitates could be dissolved again within 10 minutes in all cases.

[0089] [Example 2: Lithium-ion secondary battery] (2-1. Positive electrode) A planetary mixer was charged with 100 parts by mass of lithium cobalt oxide (manufactured by Nippon Chemical Industry Co., Ltd., product name "Cellseed C") as an active material and 3 parts by mass of acetylene black as a conductive filler, and N-methylpyrrolidone was added so that the solid concentration was 90% by mass, and the mixture was stirred and mixed for 20 minutes. Then, 1 part by mass of polyvinylidene fluoride was added based on the solid content, and the mixture was kneaded for 90 minutes at a solid concentration of 82% by mass, after which N-methylpyrrolidone was further added to adjust the viscosity, and a slurry was obtained. This slurry was used to prepare a positive electrode (basis weight: 10 mg / cm) according to a general manufacturing method for electrodes for lithium ion batteries. 2 , density 3.3g / cm 3 ) was manufactured.

[0090] (2-2. Lithium-ion secondary battery) The positive electrode obtained in (2-1), a PTFE membrane filter having a thickness of 100 μm (manufactured by Merck, product name "Omnipore JMWP04700") as a separator, and a lithium metal foil having a thickness of 100 μm as a negative electrode were laminated in this order to form an electrode laminate for a lithium ion secondary battery.

[0091] LiFSI and DMC were mixed to obtain a mixture with a ratio (molar ratio) of LiFSI:DMC=1:3. A polymer (PB) was added to the mixture to a concentration of 0.5 mass% and dissolved to obtain an electrolyte. An electrode laminate was inserted into an aluminum laminate exterior material for a battery, the electrolyte was poured, and the opening of the exterior was closed to seal the contents, obtaining a lithium secondary battery.

[0092] When the obtained secondary battery was subjected to a charge / discharge test at a rate of 0.2 C in an environment of 25° C., it exhibited a discharge capacity of 140 mAh / g in the voltage range of 4.2-3.0 V, and was capable of repeated charge / discharge.

[0093] Example 3-1: Evaluation of flame retardancy (3-1-1. Preparation of electrolyte containing flame retardant) LiTFSI, DMS, and TMP as a flame retardant were mixed to a ratio (molar ratio) of LiTFSI:DMS:TMP=1:2.4:0.6 to obtain a mixed solution. A polymer (PA) was added to this mixed solution to a concentration of 10 mass%, and dissolved to obtain an electrolyte solution. The proportion of trimethyl phosphate in this electrolyte solution was 15.4 mass%. This electrolyte solution corresponds to the electrolyte solution of Example 1-9 in which a part of DMS was replaced with TMP.

[0094] (3-1-2. Flame retardancy evaluation) 100 mg of the electrolyte obtained in (3-1-1) was placed in a stainless steel dish with a diameter of 2 cm, and the flammability was evaluated by exposing it to a burner flame and observing the state of ignition. As a result, no ignition occurred even when exposed to the burner flame.

[0095] [Example 3-2: Evaluation of flame retardancy] The electrolyte of Example 1-9 (LiTFSI:DMS=1:3, polymer (PA) 10% by mass) was evaluated for flammability in the same manner as in Example 3-1 (3-1-2). It ignited when exposed to a flame for 4 seconds. However, it naturally extinguished 2 seconds after ignition. When exposed to a flame again after extinguishing, it ignited again, but like the first time, it naturally extinguished 2 seconds after ignition. From this, it was found that although this electrolyte ignites, it does not burn completely and exhibits self-extinguishing properties.

[0096] Comparative Example 1 1M LiPF, the standard for lithium-ion batteries 6 To the electrolyte (solvent: EC and DEC, mass ratio 50:50 mixture), TMP was added to a concentration of 30% by mass to obtain a flame-retardant electrolyte. The electrolyte was evaluated for flammability in the same manner as in (3-1-2) of Example 3-1. Immediately after the flame was applied, it instantly ignited, and the combustion continued until the liquid in the dish could no longer be confirmed. After the combustion ended, the electrolyte was applied to the dish again, but no ignition occurred, so it was determined that all of the electrolyte had burned. From this, it was evaluated that this electrolyte had higher flammability than the electrolytes of Examples 3-1 and 3-2.

[0097] [Example 4: Lithium-ion secondary battery using plastic composition] (4-1. Electrolyte) LiFSI and EC were mixed at a ratio (molar ratio) of LiFSI:EC = 1:2 to obtain a mixed solution. A polymer (PB) was added to this mixed solution at a concentration of 5 mass% and dissolved to obtain an electrolyte solution.

[0098] (4-2. Plastic composition; positive electrode sheet) 10 parts by mass of the electrolyte obtained in (4-1), 1 part by mass of PTFE (powdered PTFE 6-J, average particle size 470 μm, bulk density 470 g / l, manufactured by Mitsui DuPont Fluorochemical Co., Ltd., the same applies below) as a fibrous material, 100 parts by mass of lithium cobalt oxide, and 3 parts by mass of acetylene black were weighed out and thoroughly kneaded in a mortar, resulting in a lump of clay-like plastic composition. This plastic composition was thinly spread to obtain a positive electrode sheet with a thickness of 100 μm and a thickness accuracy of ±3%. Even though this sheet had a rectangular shape of 6 cm square, it could be pinched with tweezers and had high self-supporting properties. When observed with a scanning electron microscope, a structure was confirmed in which the added PTFE became nanofibers of about several nm and bridged the particles of lithium cobalt oxide and acetylene black.

[0099] (4-3. Lithium-ion secondary battery) An aluminum foil having a thickness of 25 μm, the positive electrode sheet obtained in (4-2), a separator impregnated with the electrolyte solution obtained in (4-1) (manufactured by Polypore, product name "Celgard 2325"), a Li metal foil having a thickness of 100 μm as a negative electrode, and a copper foil having a thickness of 25 μm were stacked in this order to obtain an electrode laminate for a lithium ion secondary battery. The electrode laminate was inserted into an aluminum laminate exterior for a battery, and after degassing in a vacuum for 1 minute, the opening of the exterior was sealed with heat while maintaining the vacuum degassing state, thereby vacuum sealing the contents and producing a lithium ion secondary battery. No weight loss was observed before and after vacuum sealing. Immediately after production, this battery was charged and discharged at a rate of 0.1 C in an environment of 25°C, and showed a discharge capacity of 140 mAh / g in the voltage range of 4.2-3.0 V, and repeated charging and discharging was possible. When the battery was repeatedly charged and discharged to measure the change in capacity, it was found to maintain 90% of its initial capacity after 200 charge / discharge cycles.

[0100] [Comparative Example 2: Ionic Conductivity of Electrolyte Solutions of the Prior Art] (C2-1. Preparation of electrolyte solution according to the prior art) LiFSI and GBL were mixed in a ratio (molar ratio) of LiFSI:GBL=1:2 to obtain an electrolyte solution according to the conventional technology.

[0101] (C2-2. Measurement of ionic conductivity) The ionic conductivity of the electrolyte obtained in (C2-1) was measured. The measurement was performed at 25°C by an AC impedance method in the frequency range of 1M to 0.1Hz. As a result, the ionic conductivity was 1.28×10 -3 S / cm.

[0102] [Example 5: Ionic Conductivity of the Electrolyte Solution of the Present Invention] The polymer (PA) was added to the conventional electrolytic solution prepared in Comparative Example 2 (C2-1) so that the concentration was 5 mass%, and dissolved to prepare the electrolytic solution of the present invention. The ionic conductivity of this electrolytic solution was measured by the same measuring method as in Comparative Example 2 (C2-2). As a result, the ionic conductivity was 1.70 × 10 -3 S / cm, which was higher than that of the sample without the addition of the polymer.

[0103] [Comparative Example 3: Ionic Conductivity of Compressed Inorganic Solid Electrolyte Powder Only] LTAP (Ohara ion-conductive glass Li) as an inorganic solid electrolyte 2 O-Al 2 O 3 -SiO 2 -P 2 O 5 -TiO 2 ) powder (volume average particle size 1 μm, density 2.8 g / cm 3 A sample of 200 mg of the electrolyte was placed in a cylindrical measurement cell with a diameter of 10 mm, and a pressure of 10 MPa was applied from above and below using a pair of SUS electrodes. This pressurized state was maintained, and the ionic conductivity at 25°C was measured. The measurement was performed using an AC impedance method in the frequency range of 1 MHz to 0.1 Hz. The resulting ionic conductivity was 3.54×10 -5 S / cm.

[0104] This solid electrolyte is in the form of unground crystals, with a molecular weight of 1.5 × 10 -3On the other hand, the ionic conductivity of the compressed powder was low even when it was compressed at a high pressure of 10 MPa, as mentioned above. This is believed to be due to the fact that the contact between the powder particles is still incomplete even when compressed in this manner.

[0105] [Example 6: Ionic conductivity of insulating layer containing inorganic solid electrolyte powder] 100 mg of the electrolytic solution of the present invention obtained in Example 5 and 10 mg of PTFE fiber as a fibrous material were weighed out, and the same inorganic solid electrolyte as that used in Comparative Example 3 was weighed out so that the volume fraction of the inorganic solid electrolyte in the entire composition was 70 volume %. These were thoroughly kneaded to obtain a clay-like plastic composition. This plastic composition had self-supporting properties and plasticity. This plastic composition was molded into a sheet with a thickness of 200 μm, punched out into a disk with a diameter of 12 mm, sandwiched between two disk-shaped SUS plates, and pressurized with a pressure of 0.01 MPa. This pressurized state was maintained, and the ionic conductivity at 25 ° C. was measured. The measurement was performed in the frequency range of 1 M to 0.1 Hz by an AC impedance method. As a result, the ionic conductivity was 2.29 × 10 -3 S / cm, which was higher than the ionic conductivity measurement result for the electrolyte solution of Example 5. From this, it is considered that the main ionic conduction in this system was the solid electrolyte, and that the electrolyte solution acted as an improver for the interfacial contact of the solid electrolyte.

[0106] [Example 7: Lithium-ion secondary battery having an electrode and an insulating layer containing a fibrous material] (7-1. Electrolyte) LiFSI and SL were mixed at a ratio (molar ratio) of LiFSI:SL = 1:2 to obtain a mixed solution. A polymer (PB) was added to this mixed solution at a concentration of 5 mass% and dissolved to obtain an electrolyte solution.

[0107] (7-2. Plastic composition; positive electrode sheet) 10 parts by mass of the electrolyte obtained in (7-1), carbon nanotubes (manufactured by Zeon NanoTechnologies, product name "ZEONANO SG101", arithmetic mean diameter: 4 nm, arithmetic mean length: 400 μm, BET specific surface area: 1150 m) as a component serving as both a conductive material and a fibrous material were mixed. 2 1 part by mass of lithium sulphate (1 / g, the same applies below) and 100 parts by mass of lithium cobalt oxide were weighed out and mixed in a mortar to obtain a clay-like plastic composition. This plastic composition was thinly spread to a thickness of 80 μm, with a thickness accuracy of ±3%, and a density of 3.9 g / cm. 3 Even though this sheet had a rectangular shape of 4 cm on each side, it could be picked up with tweezers and had a high degree of self-supporting ability.

[0108] (7-3. Plastic composition; negative electrode sheet) 10 parts by mass of the electrolyte obtained in (7-1), 0.4 parts by mass of carbon nanotubes as a component that serves both as a conductive material and a fibrous material, and 40 parts by mass of graphite (604A manufactured by Nippon Carbon Co., Ltd.) as a negative electrode active material were weighed out and kneaded in a mortar, resulting in a lump of clay-like plastic composition. This plastic composition was thinly spread to obtain a negative electrode sheet with a thickness of 80 μm and a thickness accuracy of ±3%. Even though this sheet had a rectangular shape of 4 cm square, it could be picked up with tweezers and had high self-supporting properties.

[0109] (7-4. Plastic composition; insulating layer) 10 parts by mass of the electrolyte obtained in (7-1), 0.1 parts by mass of PTFE fiber as a fibrous material, and 5 parts by mass of alumina with a volume average particle size of 5 μm were weighed out and kneaded in a mortar, resulting in a lump of clay-like plastic composition. This plastic composition was thinly spread to obtain an insulating layer sheet with a thickness of 50 μm and a thickness accuracy of ±3%. Even though this sheet had a rectangular shape of 4 cm square, it could be picked up with tweezers and had high self-supporting properties.

[0110] (7-5. Lithium-ion secondary battery) An aluminum foil having a thickness of 25 μm, the positive electrode sheet obtained in (7-2), the insulating layer sheet obtained in (7-4), the negative electrode sheet obtained in (7-3), and a copper foil having a thickness of 25 μm were stacked in this order to obtain an electrode laminate for a lithium ion secondary battery. The electrode laminate was inserted into an aluminum laminate exterior for a battery, and after degassing in a vacuum for 1 minute, the opening of the exterior was sealed with heat while maintaining the vacuum degassing state, thereby vacuum sealing the contents and producing a lithium ion secondary battery. No weight loss was observed before and after vacuum sealing. Immediately after production, this battery was charged and discharged at a rate of 0.1 C in an environment of 25° C., and in the voltage range of 4.2-3.0 V, it showed a discharge capacity of 140 mAh / g relative to the positive electrode weight, and repeated charging and discharging was possible.

[0111] Example 8: Evaluation of changes in state due to volatilization of electrolyte LiFSI and DMC were mixed at a ratio (molar ratio) of LiFSI:DMC=1:1 to obtain an electrolyte solution of the prior art. Furthermore, a polymer (PB) was added to the electrolyte solution of the prior art at a concentration of 5 mass% and dissolved therein to obtain an electrolyte solution of the present invention.

[0112] Each of the electrolytes of the prior art and the present invention was weighed out in a glass dish of 1 g and left in a draft in a dry room at a temperature of 18°C ​​and a dew point of -40°C or less. When the state of the electrolytes was observed 24 hours after the start of the leaving, weight loss was confirmed in both electrolytes, and it was considered that 40% of the acetonitrile in the electrolyte had volatilized. At this point, the formation of crystals was confirmed in the electrolyte of the prior art, but not in the electrolyte of the present invention. The test was further extended for the electrolyte of the present invention, and the state was observed again 48 hours after the start of the leaving, and still no salt precipitation was confirmed. From this, it was found that the electrolyte of the present invention is less likely to cause salt precipitation even if the solvent is reduced during long-term use of the electrochemical device.

[0113] [Example 9: Bipolar structure electrochemical device] An aluminum foil having a thickness of 25 μm, a positive electrode sheet, an insulating layer sheet, a negative electrode sheet, a stainless steel foil having a thickness of 20 μm, a positive electrode sheet, an insulating layer sheet, a negative electrode sheet, and a copper foil having a thickness of 25 μm were stacked in this order to obtain an electrode laminate for a bipolar battery. The positive electrode sheet obtained in (7-2) of Example 7, the insulating layer sheet obtained in (7-4) of Example 7, and the negative electrode sheet obtained in (7-3) of Example 7 were used as the positive electrode sheet, the insulating layer sheet, and the negative electrode sheet obtained in (7-3) of Example 7. The bipolar battery produced had a configuration in which two cells were connected in series in the same exterior, and since the fluidity of the electrolyte was low, the electrolyte did not flow through the electrolyte inside, and it was possible to charge and discharge in a voltage range from 8.4 to 6 V.

[0114] Example 10: Preparation of an electrolyte by dissolving the second salt first LiFSI was provided as a first salt containing a first anion, and LiDFOB was provided as a second salt containing a second anion. 0.5 mmol (193.8 mg) of the second salt was added to 20 mmol (1.761 g) of ethylene carbonate and stirred at 50°C until it was completely dissolved. Next, 9.5 mmol (1.871 g) of the first salt was added and stirred, and the first salt was completely dissolved in 1 hour, and a mixed solution was obtained. A polymer (PB) was further added to this mixed solution to a concentration of 5 wt%, and dissolved, and the electrolyte solution of the present invention was obtained.

[0115] On the other hand, 9.5 mmol (1.871 g) of the first salt was added to 20 mmol (1.761 g) of ethylene carbonate and completely dissolved by stirring at 50° C. Then, 0.5 mmol (193.8 mg) of the second salt was added and stirred, but it did not dissolve, so the temperature was raised to 70° C. and further stirring was performed. Stirring at 70° C. was performed for 12 hours, but a completely dissolved state was still not obtained.

[0116] [Example 11: Production of electrolyte solution including a step of distilling off the solvent] An electrolyte solution having the same composition as in Example 1-2 was prepared by mixing the components at once. That is, 187.1 g (1 mol) of LiFSI, 41.1 g (1 mol) of acetonitrile, and 4.66 g of polymer (PB) were weighed into a glass flask and stirred at room temperature. It took about 3 hours to completely dissolve all the components.

[0117] On the other hand, the amount of acetonitrile was increased by 10 times, and 187.1g (1mol) of LiFSI, 411g (10mol) of acetonitrile, and 4.66g of polymer (PB) were weighed into a glass flask and stirred at room temperature, and in about 15 minutes, a solution in which all components were completely dissolved was obtained. When this solution was heated in an oil bath at 90°C and an operation of distilling off acetonitrile was performed, after 30 minutes, 9mol of acetonitrile could be distilled off, and as a result, the electrolyte of the present invention was obtained. The time required for dissolution and distillation was 45 minutes in total, and the electrolyte of the present invention could be produced in a shorter time.

Claims

1. a cation (C) which is a monovalent to trivalent metal ion; An anion (A); A solvent (SO) which is a compound having a molecular weight of 1000 or less; A soluble polymer (P) having a mass average molecular weight of more than 10,000, The content ratio of the solvent (SO) relative to 1 mole of the cation (C) is 0.5 to 4 moles, The electrolyte solution has a content of the polymer (P) of 0.5 mass% or more.

2. 2. The electrolyte according to claim 1, having a viscosity of 500 cP or more.

3. 3. The electrolyte solution according to claim 1, wherein the anion (A) is an anion containing a boron atom, a fluorine atom, a phosphorus atom, or two or more of these.

4. The anion (A) is (B(R X ) n1 -F) - , (P(R X ) n2 -F) - , (B(R X ) n3 ) - and mixtures thereof; R X represents a monovalent or divalent group, which may be the same or different when a plurality of groups are present, the monovalent group is a halogen atom, an alkyl group, an alkenyl group, an alkynyl group, or a monovalent organic ether group; the divalent group is an alkylene group, an alkenylene group, an alkynylene group, a divalent organic ether group, or an oxo group; the alkyl group, the alkenyl group, the alkynyl group, the monovalent organic ether group, the alkylene group, the alkenylene group, the alkynylene group, and the divalent organic ether group may be substituted with a halogen atom or an oxo group, or may have a heteroatom intervening in a part of the chain; n1 is R X are all monovalent, R X If one of is divalent and the other is monovalent, then it is 2; n2 is R X are all monovalent, R X If one of R is divalent and the other is monovalent, then R is 4; X If two of the are divalent and the others are monovalent, then the number is 3; n3 is R X are all monovalent, R X If one of R is divalent and the other is monovalent, then R is 3; X If two of the are divalent, then the value is 2. The electrolyte according to claim 3.

5. The anion (A) is PF 6 - , B.F. 4 - 5. The electrolyte of claim 4, comprising an anion selected from the group consisting of difluoro(oxalato)borate ions, bisoxalatoborate ions, and mixtures thereof.

6. The electrolyte solution according to any one of claims 1 to 5, wherein the solvent (SO) contains a flame-retardant solvent selected from the group consisting of trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, trimethyl phosphite, triethyl phosphite, tripropyl phosphite, tributyl phosphite, triphenyl phosphate, triphenyl phosphite, a phosphazene-containing compound, a substituted compound having a substituent in a part of the hydrocarbon chain of these compounds, and a mixture thereof.

7. The electrolyte solution according to any one of claims 1 to 6, wherein the polymer (P) is a copolymer.

8. The electrolyte solution according to any one of claims 1 to 7, wherein the cation (C) contains a divalent or trivalent metal ion.

9. The electrolyte solution according to any one of claims 1 to 8, wherein the polymer (P) has a mass average molecular weight of 100,000 or more.

10. A method for producing the electrolyte solution according to any one of claims 1 to 9, The production method includes a step of dissolving one or more materials containing the cation (C) and the anion (A), and the polymer (P) in the solvent (SO).

11. The anion (A) includes a first anion (A1) and a second anion (A2), The first anion (A1) is an anion contained in the anion (A) at the largest molar ratio, the second anion (A2) is an anion having a molar ratio next to that of the first anion in the anion (A), The method according to claim 10, comprising the steps of adding a salt containing the second anion (A2) to the solvent (SO), and then adding a salt containing the first anion (A1).

12. The method according to claim 10 or 11, comprising dissolving a salt containing the cation (C) and the anion (A) in the solvent (SO), and then distilling off the solvent (SO).

13. A plastic composition for an electrochemical device, comprising the electrolyte solution according to any one of claims 1 to 9 and a solid material, and having plasticity.

14. The plastic composition of claim 13 , wherein the solids comprise an active material.

15. The plastic composition of claim 13 , wherein the solid material comprises an inorganic solid electrolyte (SE).

16. The plastic composition of any one of claims 13 to 15, wherein the solid material comprises a fibrous material.

17. 17. The plastic composition of claim 16, wherein the fibrous material has an average fiber diameter of 100 nm or less.

18. 18. The plastic composition of claim 16 or 17, wherein the fibrous material is selected from the group consisting of polytetrafluoroethylene fibers, cellulose nanofibers, carbon nanotubes, and combinations thereof.

19. The plastic composition according to any one of claims 16 to 18, wherein the fibrous material is a single-walled carbon nanotube.

20. The plastic composition according to any one of claims 13 to 19, wherein the solid material comprises a particulate solid material and a fibrous material, and the fibrous material is present in a state of bridging between particles of the particulate solid material.

21. An electrode sheet for electrochemical devices, comprising the plastic composition according to any one of claims 13 to 20.

22. An insulating layer for an electrochemical device comprising the plastic composition according to any one of claims 13 to 20.

23. A method for producing an electrode sheet for electrochemical devices, comprising forming the plastic composition according to any one of claims 13 to 20 into the shape of an electrode sheet.

24. A method for producing an insulating layer for an electrochemical device, comprising molding the plastic composition according to any one of claims 13 to 20 into the shape of an insulating layer.

25. An electrochemical device comprising the electrode sheet for electrochemical devices according to claim 21, the insulating layer for electrochemical devices according to claim 22, or both of them.

26. 26. The electrochemical device of claim 25 which is of the bipolar type.

Citation Information

Patent Citations

  • Non-aqueous electrolyte and non-aqueous electrolyte secondary battery

    JP2002359000A

  • Electrolytic solution for nonaqueous secondary batteries, and nonaqueous secondary battery

    JP2015026589A

  • High-viscosity electrolyte containing salt in which alkali metal, alkaline earth metal or aluminum serves as cation, and organic solvent having hetero element

    JP2015133312A

  • Water-based electrolytic solution for power storage device and power storage device including the same

    JP2017126500A

  • Nonaqueous secondary battery, and nonaqueous electrolyte used therefor

    JP2017188299A